Collaborating with teachers to design and implement assessments for self-regulated learning in the context of authentic classroom writing tasks. Issue 4 (3rd July 2020) - Perry, Nancy E.; Lisaingo, Simon; Yee, Nikki; Parent, Natasha; Wan, Xinke; Muis, Krista
ABSTRACT: We present data from a larger longitudinal study, focusing on researchers' and teachers' collaborative design and implementation of assessments for learning (AfL), including student self-assessments, to support self-regulated learning (SRL) during classroom writing activities. We focus on students (N = 112) when they were in Grade 3. The study used a mixed method triangulation approach. Data include: detailed descriptions of classrooms with relatively high and low emphasis on SRL; students' self-assessments of SRL; and students' writing processes and products from a teacher-researcher co-constructed writing task. Students enrolled in classrooms with high emphases on SRL had more opportunities and support for SRL and A f L and, consequently, demonstrated more sophisticated self-assessments and higher levels of interest and task value than their peers in classrooms with low emphasis on SRL. Also, these learners demonstrated higher levels of self-regulation in writing tasks and higher quality writing products. Implications for research and practice are discussed.